Answer:
See explanation
Step-by-step explanation:
![(x^2+9x+10)(x-2)= \\\\x^3-2x^2+9x^2-18x+10x-20= \\\\x^3+7x^2-8x-20](https://tex.z-dn.net/?f=%28x%5E2%2B9x%2B10%29%28x-2%29%3D%20%5C%5C%5C%5Cx%5E3-2x%5E2%2B9x%5E2-18x%2B10x-20%3D%20%5C%5C%5C%5Cx%5E3%2B7x%5E2-8x-20)
Jimmy is incorrect.
Using long division, you can find that the real answer.
First, subtract
from the original expression, leaving you with
.
Next, subtract
from the expression, leaving you with
. Finally, subtract
from the expression, leaving you with a remainder of 0. This means that the real quotient is
. Hope this helps!
Answer:
y=2x+6
Step-by-step explanation:
y=2x+6 you are welcome!!
Answer:
1m
Step-by-step explanation:
hope that helps
Explica la pregunta mejor porfavor. No la entiendo
The inverse of this function is y = x - ![\frac{3}{4}](https://tex.z-dn.net/?f=%20%5Cfrac%7B3%7D%7B4%7D%20%20)
You can find the inverse of any function by switching the x and y values and then solving for the new y value. Once you've done that, what will be left over is the inverse function.
y =
----> Swap x and y
x =
-----> Subtract 3/4 from both sides.
x -
= y ----> rearrange to appropriate order
y = x - ![\frac{3}{4}](https://tex.z-dn.net/?f=%20%5Cfrac%7B3%7D%7B4%7D%20%20)
And that is your inverse function.